Full-space spin-decoupled versatile wavefront manipulations using non-interleaved metasurface - Wang, Chaohui (2023)
Achieving multifunctional wavefront manipulations of waves with a flat and thin plate is pivotal for high-capacity communications, which however is also challenging. A multi-layer metasurface with suppressed mode crosstalk provides an efficient recipe primarily for circular polarization, but all multiple functionalities still are confined to locked spin states and modes. Here, a multifunctional metasurface with spin-decoupled full-space wavefront control is reported by multiplexing both linear momentum and frequency degree of freedom. We employed vertically cascaded quadrangular patches and crossbars to integrate both geometric and dynamic phases and realized four channels between two spin states and two frequencies in distinct scattering modes (transmission and reflection). For verification, a proof-of-concept metadevice with four-port wavefront manipulations is experimentally demonstrated, exhibiting distinct functionalities including spin- and frequency-dependent focusing, quad-beam radiation, anomalous reflections, and Bessel beam generation. Our finding of full-space spin-decoupled metasurfaces would be important for high-capacity communications, multifunctional radar detections, and other applications.